Gestão de estacionamentos através de aplicação web - Marra, Matheus Felipe (2017)
This work presents the implementation of a Web application for parking lot control, which can maintain records, generate logs, keep clients data and produce parking receipt print, being compatible with most current devices. The development of this application consists in requirements gathering alongside an branch company administrator and the application development, which can be separated in two stages: server and client. For the server development, the language PHP was used, alongside the framework Laravel. For the Client development, the languages HTML, CSS and Javascript were used, through the framework Bootstrap and the library JQuery.